2009
DOI: 10.1007/s12052-009-0147-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Students at a Private Christian Liberal Arts University Toward the Teaching of Evolution

Abstract: Students at private Christian colleges tend to have a viewpoint that incorporates faith and belief in God.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…In fact, the larger their change towards the right‐hand end of the spectrum, the less they agreed that their change was due to alterations in their religious beliefs. The educational implications of this finding are that learning how evolution has been constructed through scientifically valid evidence may enable learners to perceive evolution in more sophisticated ways, leading to greater open‐mindedness to learn and accept evolution (Ladine, ). In addition, learning that there are compatible ways in which science and religion can be related may avoid threats to their religious beliefs (Yasri & Mancy, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the larger their change towards the right‐hand end of the spectrum, the less they agreed that their change was due to alterations in their religious beliefs. The educational implications of this finding are that learning how evolution has been constructed through scientifically valid evidence may enable learners to perceive evolution in more sophisticated ways, leading to greater open‐mindedness to learn and accept evolution (Ladine, ). In addition, learning that there are compatible ways in which science and religion can be related may avoid threats to their religious beliefs (Yasri & Mancy, ).…”
Section: Discussionmentioning
confidence: 99%
“…When students change their position, knowing to what factors they attribute their change is crucial for education as this should help teachers and lecturers communicate evolution in more diplomatic ways. Three key types of reasons for changes are referred to in the literature as influential: changes in understanding of the evidence for evolution (Downie & Barron, 2000; € Ozay K€ ose, 2010; Southcott & Downie, 2012;Winslow et al, 2011), changes in understanding of the relationship between science and religion (Ladine, 2009;Reiss, 2009;Yasri & Mancy, 2014) and specifically the relationship between evolution and religious beliefs, and changes in religious beliefs (Dagher & Boujaoude, 1997;Downie & Barron, 2000). These reasons represent scientific, philosophical, and religious reasons, respectively, and their relative roles have not been compared in a single study.…”
Section: Reasons For Changes In Positionsmentioning
confidence: 99%
“…Long (: 136) reports one student describing his grandfather as saying “that's evil, that's the work of the Devil” when watching a program about evolution. Most students in another study at a private Christian university have heard incorrect negative statements about evolution, such as that it is responsible for the Nazi regime, eugenics, and that is necessitates atheism (Ladine, ).…”
Section: Obstacles To Teaching and Learning Evolutionmentioning
confidence: 99%
“…Yet two other studies found no evidence that evolution instruction increases students’ acceptance of evolution (Bishop and Anderson , Lawson and Worsnop, ), and several researchers state that students’ beliefs tends to persist despite explicit attempts to improve acceptance of evolution (Nehm and Schonfeld, ; Kelemen, ). Short and Hawley () suggest that exposure to evolution in a single course is not adequate to alter students’ levels of evolution understanding or acceptance, and in one study the level of understanding of evolution was correlated with the number of college science courses the students had taken (Ladine, ). The only study on graduate students in different sciences showed a correlation between acceptance and both self‐assessed and actual levels of understanding of evolution (Gregory and Ellis, ).…”
Section: Obstacles To Teaching and Learning Evolutionmentioning
confidence: 99%
“…Other papers provide examples of interdisciplinary and integrative programs for reaching a broad range of students (O'Brien et al 2009;Nadelson et al 2009). This issue also includes papers highlighting the connection between understanding the Nature of Science and evolution (Ladine 2009;McCrory and Murphy 2009). NCSE provides information on the value and impact of science standards in their regular column and a report on current science standards (Scott 2009;Mead and Mates 2009), which is nicely complimented by a paper about a successful professional development program that reaches out to include school boards and administrators (Johnson et al 2009).…”
mentioning
confidence: 99%